The Role of Cardiopulmonary Bypass on the Early Postoperative IgG levels, Effect on the Postoperative Outcome in Cardiac Surgery Patients - A Pilot Study (Cardiovascular Journal, 2015)
Objective: This study tried to elucidate the role of the cardiopulmonary bypass on the early postoperative immunoglobulin G levels and any probable effects on the postoperative outcome of the patients. Methods: 99 consecutive patients were studied. The evening after surgery the level of the immunoglobulin G was obtained. The postoperative course of each patient during the first three days was followed. One way ANOVA was used for statistical analysis. Results: 20 (20.2%) patients had decreased early postoperative immunoglobulin G levels. 87 (87.87%) patients were operated with cardiopulmonary bypass and 17 (19.54%) of them had lower levels of postoperative immunoglobulin G without any significantly increased clinically adverse events. The statistical analysis between the two groups included: pulmonary infiltrations, leukocytosis >15x103/mm3, pulmonary dysfunction, mechanical ventilation >24h, renal and hepatic dysfunction, postoperative ileus, postoperative delirium, sternal wound infection, thrombocytopenia